Radiocesium metabolism in reindeer - Jones, Bernt-E. V.; Eriksson, Olof; Nordkvist, Magnus (Rangifer, 1990)
Abstract: Early in the era of atmospheric nuclear weapon tests, the reindeer was found to be an interesting animal concerning the transfer of environmental radioactive contaminants to man via the production of contaminated reindeer meat. The reason for the high transfer factors for some radionuclides is the feeding habits of the reindeer with a substantial intake of lichens, especially in the wintertime. One effect of the seasonal changes in feeding is also a considerable cyclic, seasonal variation in radiocesium content of soft tissues. The effective half-life of radiocesium was determined to about 30 days in an experiment where a herd of reindeer was moved form a high (>20 kBq/m2137Cs) to a low (<3 kBq/m2 137Cs) contamination area. The fractional transfer of 137Cs, during natural grazing, was determined to about 0.65 d/kg during wintertime on the low- contamination area and about 0.30 d/kg in summertime grazing in a more contaminated area. The radiation dose received by reindeers in Sweden after the Chernobyl accident was calculated to <200 mSv/a. The dose rate would be highest during the later part of winter but would not exceed 1 mSv/d.